Immorality - Milo, Ronald D. (Ronald Dmitri), 1935- (Studies in moral, political, and legal philosophy., 1984)
This book explores a much-neglected area of moral philosophy--the typology of immorality. Ronald D. Milo questions the adequacy of Aristotle's suggestion that there are two basic types of immorality--wickedness and moral weakness--and argues that we must distinguish between at least six different types of immoral behavior. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve.